2021
DOI: 10.3389/fphar.2021.652412
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Oral Liquids Combined With Azithromycin for Mycoplasma pneumoniae Pneumonia in Children: A Bayesian Network Meta-Analysis

Abstract: Background:Mycoplasma pneumoniae pneumonia (MPP) causes flu-like symptoms in children, increasing the burden on the health and education systems. In China, traditional Chinese medicine oral liquids (TCMOLs) combined with azithromycin (TCMOLs + Azithromycin) is commonly used to treat MPP in children. However, TCMOLs with the optimal clinical applicability remain unknown. Here, we evaluated the clinical effectiveness and safety of TCMOLs + Azithromycin in children with MPP.Methods: We searched PubMed, Embase, Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(42 reference statements)
0
3
0
Order By: Relevance
“… 14 While MPP is generally benign and mild, severe or prolonged infections can lead to extrapulmonary manifestations, affecting systems such as the digestive, cardiovascular, and nervous systems. 15 The host-pathogen interactions play a significant role in signaling and physiological changes within host cells and can induce post-transcriptional regulation of genes involved in immune and inflammatory responses, and the regulation of microRNAs (miRNAs) is closely related to infectious diseases. 16 Macrolide antibiotics, particularly azithromycin, are commonly used as the first-line treatment for MPP in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 14 While MPP is generally benign and mild, severe or prolonged infections can lead to extrapulmonary manifestations, affecting systems such as the digestive, cardiovascular, and nervous systems. 15 The host-pathogen interactions play a significant role in signaling and physiological changes within host cells and can induce post-transcriptional regulation of genes involved in immune and inflammatory responses, and the regulation of microRNAs (miRNAs) is closely related to infectious diseases. 16 Macrolide antibiotics, particularly azithromycin, are commonly used as the first-line treatment for MPP in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…even recruited patients regardless of the disease intensity. Secondly, the included interventions for MPP were not strict because extra medications such as acupuncture or special nursing were used in some studies [ 28 , 30 ]. Thirdly, an observational study with controls, in which the patients were grouped by therapy regimens [ 27 ], could not be identified as an RCT, because it is highly likely that this was a retrospective analysis of clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the combination of TCMs with azithromycin was demonstrated to be more efective in the treatment of pediatric MPP. Although some studies lack sufcient evidence for higher safety, most meta-analytic studies suggested that TCMs combined with azithromycin have better clinical efcacy and fewer side efects in the treatment of MPP among children [69][70][71][72][73]. In China, MSD was commonly used in the clinical treatment of upper respiratory tract infections, pneumonia, and bronchial asthma, and accumulating studies revealed that MSD or MSD with western medicine also showed positive therapeutic benefts on MPP in children [15,74].…”
Section: Journal Of Clinical Pharmacy and Terapeuticsmentioning
confidence: 99%
“…For MPP in children, TCMs are generally efective in relieving cough, fever, and pulmonary rales. Tis is refected in many oral liquids [72], Chinese herb injections [71] investigations, including liquiritin, glycyrrhizin, glycyrrhetinic acid, amygdalin, sagoside, ephedrine, pseudoephedrine, and methylephedrine [75]. Interestingly, a recent study found that MSD mitigates MPP-induced pyroptosis via the NLRP3 infammasome [15].…”
Section: Journal Of Clinical Pharmacy and Terapeuticsmentioning
confidence: 99%